2011
DOI: 10.1258/ar.2011.110020
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hypoplasia of bony cochlear nerve canal by virtual endoscopy: a pilot study

Abstract: The absence of a helix-like shape at VE images may be used as a potentially useful sign in the diagnosis of hypoplasia of BCNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They found narrow BCNCs in more than half of the ears with SNHL, which indicated a significant association between BCNC stenosis and cochlear hypoplasia. In the presence of normal cochleae, BCNC stenosis has also been reported to be a potential cause of congenital SNHL [12][13][14] . The studies that arrived at this conclusion typically referred to BCNC as a potential anatomical site for the evaluation of bony inner ear structures with temporal bone CT.…”
Section: Discussionmentioning
confidence: 99%
“…They found narrow BCNCs in more than half of the ears with SNHL, which indicated a significant association between BCNC stenosis and cochlear hypoplasia. In the presence of normal cochleae, BCNC stenosis has also been reported to be a potential cause of congenital SNHL [12][13][14] . The studies that arrived at this conclusion typically referred to BCNC as a potential anatomical site for the evaluation of bony inner ear structures with temporal bone CT.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been three studies in which the investigators observed the fundus of IAC and foramina of superior and inferior vestibular, facial, and cochlear nerve with VE (10,14,16), only one study has described the morphology of BCNC (16).…”
Section: Introductionmentioning
confidence: 99%
“…CT virtual endoscopy (VE) is an image processing technique that allows for non-invasive visualization of the surface or the content of the volume by threedimensional (3D) reconstruction of CT data and its role in imaging temporal bone anatomy has been discussed (9)(10)(11)(12)(13)(14)(15)(16). Although there have been three studies in which the investigators observed the fundus of IAC and foramina of superior and inferior vestibular, facial, and cochlear nerve with VE (10,14,16), only one study has described the morphology of BCNC (16).…”
Section: Introductionmentioning
confidence: 99%